The Roles of Large Top Predators in Coastal Ecosystems: New Insights from Long Term Ecological Research - William J. Ripple; James C. Nifong; Philip Matich; Martha E. Mather; Michael R. Heithaus; Adam E. Rosenblatt; Brian R. Silliman (Oceanography, 2013)
During recent human history, human activities such as overhunting and habitat destruction have severely impacted many large top predator populations around the world. Studies from a variety of ecosystems show that loss or diminishment of top predator populations can have serious consequences for population and community dynamics and ecosystem stability. However, there are relatively few studies of the roles of large top predators in coastal ecosystems, so that we do not yet completely understand what could happen to coastal areas if large top predators are extirpated or significantly reduced in number. This lack of knowledge is surprising given that coastal areas around the globe are highly valued and densely populated by humans, and thus coastal large top predator populations frequently come into conflict with coastal human populations. This paper reviews what is known about the ecological roles of large top predators in coastal systems and presents a synthesis of recent work from three coastal eastern US Long Term Ecological Research (LTER) sites where long-term studies reveal what appear to be common themes relating to the roles of large top predators in coastal systems. We discuss three specific themes: (1) large top predators acting as mobile links between disparate habitats, (2) large top predators potentially affecting nutrient and biogeochemical dynamics through localized behaviors, and (3) individual specialization of large top predator behaviors. We also discuss how research within the LTER network has led to enhanced understanding of the ecological roles of coastal large top predators. Highlighting this work is intended to encourage further investigation of the roles of large top predators across diverse coastal aquatic habitats and to better inform researchers and ecosystem managers about the importance of large top predators for coastal ecosystem health and stability.